Pengaruh Green Accounting, Environmental Performance, dan Nilai Perusahaan: Bukti Empiris pada Perusahaan Sektor Industri Dasar dan Kimia - Faisal Hasbullah Batubara; Wahyu Widjayanti; Sulistining Trimulyani; Budi Utami (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to examine the effect of green accounting and environmental performance on firm value in Basic Materials and Chemicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study is motivated by the growing demand for sustainable business practices and the inconsistent findings of previous studies regarding the influence of environmental accounting and environmental performance on firm value. A quantitative research approach was employed using secondary data obtained from annual reports, sustainability reports, and the Corporate Performance Rating Program in Environmental Management (PROPER) reports. The sample was selected using a purposive sampling technique, resulting in 10 companies with a total of 30 observations. Data were analyzed using panel data regression with EViews, including descriptive statistical analysis, panel data model selection, classical assumption tests, hypothesis testing, and the coefficient of determination test. The results indicate that green accounting has a negative and significant effect on firm value, with a regression coefficient of -0.082843 and a probability value of 0.0005 (p < 0.05). Meanwhile, environmental performance has no significant effect on firm value, with a regression coefficient of 0.076177 and a probability value of 0.8394 (p > 0.05). Simultaneously, green accounting and environmental performance have a significant effect on firm value, as indicated by a Prob(F-statistic) of 0.000468 (p < 0.05). The Adjusted R² value of 0.3913 indicates that these two variables explain 39.13% of the variation in firm value, while the remaining 60.87% is explained by other factors outside the research model. This study provides an empirical contribution by enriching the literature on the role of green accounting and environmental performance in influencing firm value, particularly in companies within the Basic Materials and Chemicals sector. Furthermore, the findings serve as a practical reference for companies in optimizing the implementation of sustainable business practices to enhance firm value.